Trends and challenges of multi-drug resistance in childhood tuberculosis - Zhuang, Zengfang; Sun, Lin; Song, Xiaorui; Zhu, Hanzhao; Li, Lianju; Zhou, Xintong; Mi, Kaixia (Frontiers in Cellular and Infection Microbiology, 2023)
The global epidemic of multidrug-resistant tuberculosis (MDR-TB) in children is an urgent challenge for treatment and diagnosis. Here, we summarize the current literature on drug resistance in Mycobacterium tuberculosis (the pathogen that causes tuberculosis) and provide an overview of some drug resistance solutions in use or under development for pediatric tuberculosis, as well as risk assessments. The accurate determination of the drug resistance spectrum of M. tuberculosis is very important for the correct treatment of tuberculosis in children. In addition, the treatment of children with multidrug-resistant tuberculosis will be expanded to include the evaluation of new drugs or new combinations of drugs, including the evaluation of the safety of drug combinations, immunotherapy and antibody drugs. Finally, basic research is needed to support the technological development of biomarkers to assess the phase of therapy, which is fundamental to solving the problem of drug resistance in children.